EFFECT OF POSITIONAL RELEASE TECHNIQUE IN SUBJECTS WITH SUBACUTE TRAPEZITIS (International Journal of Physiotherapy, 2014)
Background: Trapezius stretching combined with positional release technique (PRT) have found effective in trapezitis, studies are limited to find which technique has shown effective over the other due to lack of control group. The purpose of the study is to find the effect of PRT on pain intensity, functional disability and range of motion in subjects with subacute trapezitis.Method: An experimental study design, selected subjects with subacute trapezitis was randomized into Study and Control group. Total 40 subjects, 20 subjects in each group; data was collected who completed the study. Control group received passive trapezius muscle stretching while Study group received positional release technique with passive trapezius muscle stretching for 8 sessions in 2 weeks. Outcome measurements such as Visual Analogue scale, Neck disability index and cervical Range of motion were measured.Results: There is statistically significant difference (p